Analisis Peran Kontribusi Koperasi Syariah dalam Pengembangan UMKM di Kota Pekalongan - Himma Arasy Attamimi; Amalia Ayuningtyas; Nailis Syafa Kamila; David Apriyansyah; Diah Ayu Eka Putri (Journal of Islamic Economics and Finance, 2023)
Micro, small and medium enterprises (MSMEs) are productive business units that can stand alone and are carried out by individuals or business entities in all economic sectors that have been able to survive amid the economic crisis that has hit since 1997 and have even become a lifeline for the country's economic recovery. In the city of Pekalongan, cooperatives can play an important role in community businesses, such as MSMEs. This is an effort to overcome poverty in society. This research uses a descriptive qualitative approach. The data used in this research is primary and secondary data. Primary data was obtained from interviews with MSMEs in Pekalongan City and secondary data was obtained from various sources, namely from the Central Statistics Agency (BPS), the Financial Services Authority (OJK), journals and articles relevant to research. Sharia cooperatives have products and mechanisms that are based on the Koran and the hadith of the Prophet. In its implementation, the cooperative system is able to provide loans that are far from the interest element which is clearly prohibited by the Shari'a. Cooperatives have various contracts that can guarantee the smooth transaction process for MSMEs that need funds or MSMEs who want to save their funds. From these interviews, the role of cooperatives in terms of MSME capital has great potential. Cooperatives can be a driving force in the growth of the real sector, especially MSMEs. With the presence of cooperatives, it helps the community, especially MSMEs, in realizing and developing their business. Apart from that, cooperative activities do not contain elements of usury, gharar and maysir.